Fast, ultrasensitive detection of reactive oxygen species using a carbon nanotube based-electrocatalytic intracellular sensor - Rawson, Frankie J.; Hicks, Jacqueline; Dodd, Nicholas; Abate, Wondwossen; Garrett, David J.; Yip, Nga-Chi; Fejer, Gyorgy; Downard, Alison J.; Baronian, Kim H.R.; Jackson, Simon K.; Mendes, Paula M. (American Chemical Society, 2015)
Herein, we report a highly sensitive electrocatalytic sensor-cell construct that can electrochemically communicate with the internal environment of immune cells (e.g., macrophages) via the selective monitoring of a particular reactive oxygen species (ROS), hydrogen peroxide. The sensor, which is based on vertically aligned single-walled carbon nanotubes functionalized with an osmium electrocatalyst, enabled the unprecedented detection of a local intracellular “pulse” of ROS on a short second time scale in response to bacterial endotoxin (lipopolysaccharide-LPS) stimulation. Our studies have shown that this initial pulse of ROS is dependent on NADPH oxidase (NOX) and toll like receptor 4 (TLR4). The results suggest that bacteria can induce a rapid intracellular pulse of ROS in macrophages that initiates the classical innate immune response of these cells to infection.